#### Answer

$12$

#### Work Step by Step

RECALL:
(i) $a^m \cdot a^n = a^{m+n}$
(ii) $a^{0} = 1, a \ne 0$
Use the rules above to have:
$=12x^{2+(-2)}
\\=12x^0
\\=12(1)
\\=12$

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

$12$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.